Room : a novel - Donoghue, Emma, 1969- (New York : Little, Brown and Co., 2010)
Narrator Jack and his mother, who was kidnapped seven years earlier when she was a 19-year-old college student, live in a tiny, 11-foot-square shed in the kidnapper's yard. But Ma, as Jack calls her, proves to be resilient and resourceful--and attempts a nail-biting escape.
Keywords: Boys -- Fiction; Mother and child -- Fiction; Kidnapping -- Fiction; Psychopaths -- Fiction; Escapes -- Fiction; Suspense fiction